Analisis Teknik Permainan Gitar Klasik Romance De Amour Oleh Tiga Gitaris Alumni Fakultas Bahasa Dan Seni Universitas HKBP Nommensen Medan - Daniel Rizky Anderson; Simajuntak , Hendrik L; Simangunsong, Emmi (Visi Sosial Humaniora, 2025)
This study aims to analyze classical guitar techniques in the piece Romance de Amor as performed by three alumni guitarists. The piece is known by various titles, including Romance Anónimo, Spanish Romance, and Estudio en Mi de Rubira, and has become a significant repertoire in the classical guitar world. The research method employed is descriptive qualitative, using a case study approach based on the recordings of the three alumni guitarists. Data were collected through observation, documentation, and technical analysis of right- and left-hand techniques, as well as the musical interpretations presented. The analysis focuses on elements such as triplet-based arpeggio patterns, the use of apoyando and tirando techniques, and dynamics in expressing the transition from E minor to E major. The findings show that although all three guitarists applied similar fundamental techniques, differences in musical interpretation reflect the uniqueness of each guitarist's style. These differences include variations in tempo, articulation, and melodic emphasis, demonstrating how basic techniques can be shaped into distinct interpretations. This study provides insight into the importance of mastering fundamental techniques in creating expressive and personal musical interpretations.